3D and 2D structural characterization of 1D Al/Al2O3 biphasic nanostructures. (21st January 2015) - MIRÓ, M. MARTINEZ; VEITH, M.; LEE, J.; SOLDERA, F.; MÜCKLICH, F.; BENNEWITZ, R.; AKTAS, C.
Summary 1D Al/Al2O3 nanostructures have been synthesized by chemical vapour deposition (CVD) of the molecular precursor [tBuOAlH2]2. The deposited nanostructures grow chaotically on the substrate forming a layer with a high porosity (80%). Depending on the deposition time, diverse nanostructured surfaces with different distribution densities were achieved. A three‐dimensional (3D) reconstruction has been evaluated for every nanostructure density using the Focus Ion Beam (FIB) tomography technique and reconstruction software tools. Several structural parameters such as porosity, Euler number, geometrical tortuosity and aspect ratio have been quantified through the analysis with specified software of the reconstructions. Additionally roughness of the prepared surfaces has been characterized at micro‐ and nanoscale using profilometry and AFM techniques, respectively. While high aspects ratio around 20–30 indicates a strong anisotropy in the structure, high porosity values (around 80%) is observed as a consequence of highly tangled geometry of such 1D nanostructures.